Iodine-Catalyzed Synthesis of Alkylthio-Substituted 1,4-Enediones from Styrenes and Dialkyl Sulfoxides - Rastogi, Gaurav K.; Deb, Mohit L.; Baruah, Pranjal K. (Synthesis, 2022)
We have developed an efficient iodine-catalyzed route for the synthesis of 2-(alkylthio)-substituted 1,4-enedione derivatives from styrenes under an open air atmosphere. Styrenes are heated with a range of sulfoxides in the presence of iodine and potassium persulfate to afford the desired products in high yields. Except for DMSO, all the sulfoxides are synthesized in the laboratory and are used crude. The products are formed as mixtures of E and Z stereoisomers that are easily separable by column chromatography. Both oxygen atoms of 1,4-enedione product originate from aerial oxygen. A mechanism is proposed based on control experiments and literature reports.
Keywords: styrenes; sulfoxides; 1,4-enediones; iodine; aerial oxygen; phenacyl iodide